2021
DOI: 10.3390/biomedicines9020145
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Impact of Microbiota in the Treatment of NAFLD/NASH and Its Potential as a Biomarker for Prognosis and Diagnosis

Abstract: Non-alcoholic fatty liver disease (NAFLD) is an increasing cause of chronic liver illness associated with obesity and metabolic disorders, such as hypertension, dyslipidemia, or type 2 diabetes mellitus. A more severe type of NAFLD, non-alcoholic steatohepatitis (NASH), is considered an ongoing global health threat and dramatically increases the risks of cirrhosis, liver failure, and hepatocellular carcinoma. Several reports have demonstrated that liver steatosis is associated with the elevation of certain cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 134 publications
0
14
0
Order By: Relevance
“…56,57 Accumulating evidence indicated that gut microbial dysbiosis was associated with the pathogenesis of MAFLD, 58 which was related to low-grade inflammation. 59 Therefore, GGT/HDL was closely correlated with MAFLD.…”
Section: Discussionmentioning
confidence: 96%
“…56,57 Accumulating evidence indicated that gut microbial dysbiosis was associated with the pathogenesis of MAFLD, 58 which was related to low-grade inflammation. 59 Therefore, GGT/HDL was closely correlated with MAFLD.…”
Section: Discussionmentioning
confidence: 96%
“…Diet has a considerable effect on the composition of gastrointestinal microbiota and an unhealthy diet, among other factors, alters its composition and induces gastric microbial dysbiosis [ 52 ]. The gut microbiome is the genetic material of all the microbes that live on and inside the human body [ 53 , 54 , 55 ]. H. pylori colonization results in the alteration of gastric microbiota and a reduction in bacterial diversity [ 56 , 57 ], thus modifying the host’s gut microbiome [ 58 ].…”
Section: The Impact Of Diet Patterns In Helicobacter Pylori Infectionmentioning
confidence: 99%
“…They have also been linked to the prevention and treatment of cardiovascular diseases like hypertension [ 8 , 9 ], along with enhanced predisposition towards various viral and bacterial infections. In various other studies, these “healthy” microbiota have been associated with the treatment of various metabolic diseases like obesity [ 10 , 11 ], diabetes, and nonalcoholic fatty liver disease (NAFLD) [ 12 ]. The emerging role of these microbiota has also been reported as a mitigation strategy against various respiratory viral infections [ 13 ] including COVID-19 [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%